The Influence of Information Systems and Artificial Intelligence (AI) on Human Resource Performance - Seth, Sameer; Raihan Saputra (International Journal of Advanced Multidisciplinary, 2023)
The article on the influence of information systems and artificial intelligence (AI) on human resource performance is a scientific literature article in the scope of human resource management science. The purpose of this writing is to build a hypothesis regarding the influence between variables that can later be used for further research in the scope of human resource management. The research method used is descriptive qualitative. The data used in this descriptive qualitative approach comes from previous research that is relevant to this research and is obtained from online academic media such as Taylor & Francis, Scopus Emerald, Web of Science, Sinta Journal, DOAJ, EBSCO, Google Scholar, and digital reference books. The results of this article are: 1) Information systems have an impact on human resource performance; 2) Artificial intelligence (Ai) has an impact on human resource performance.